The Effects of Entrepreneurial Competency and Entrepreneurial Orientation on Micro and Small Enterprise Business Performance Through Behavioral Commitment in South Manokwari Regency, West Papua - Suharsono, Desi Suharnani; Ansar, Ansar; Gunawan, Gunawan; Kurniawaty, Kurniawaty (Journal Development Manecos, 2026)
This study aims to examine the effects of entrepreneurial competency and entrepreneurial orientation on business performance through behavioral commitment among Micro and Small Enterprises in South Manokwari Regency, West Papua Province. A quantitative research approach was employed using a survey method. The population consisted of 830 Micro and Small Enterprises, and 168 respondents were selected through purposive sampling. Data were collected using structured questionnaires and analyzed using Partial Least Squares Structural Equation Modeling. The findings indicate that entrepreneurial competency and entrepreneurial orientation have positive and significant effects on behavioral commitment and business performance. Behavioral commitment also has a positive and significant effect on business performance. Furthermore, behavioral commitment significantly mediates the relationship between entrepreneurial competency and business performance as well as the relationship between entrepreneurial orientation and business performance. The results suggest that entrepreneurs possessing higher levels of knowledge, managerial capability, innovativeness, proactiveness, and risk-taking behavior tend to demonstrate stronger commitment toward business activities, which subsequently contributes to improved business performance. The study concludes that entrepreneurial competency and entrepreneurial orientation represent important strategic resources that enhance business performance directly and indirectly through behavioral commitment. These findings provide empirical evidence regarding the importance of strengthening entrepreneurial capabilities and commitment to improve the competitiveness and sustainability of Micro and Small Enterprises in regional economic contexts.